2021
DOI: 10.3390/su13020559
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Environmental Disaster Movies on Corporate Environmental and Financial Performance

Abstract: Using a unique United States box office data set, we investigate the impact of environmental sentiment on corporate environmental and financial performance of the United States listed firms. The influence of mass media on public and investor sentiments is well documented in the existing literature. However, little is known about the effect of movies, although they may influence the public more than other mass media because people, regardless of age and gender, enjoy watching movies. Using the event study metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 63 publications
1
10
0
Order By: Relevance
“…If sample size will be greater than answer may become similar to previous researches. Third, industry competition has positive significant moderating effect on the association between CER and CFP which is similar to previous researches like Hull (2008), who said if competition is high in industry then it will urge companies to attract more customers and investors towards them which is possible if they provide convenience to them by providing safe environment and ultimately it will create long term revenue for the company (Kim & Park, 2021;Lee et al, 2021;Wu et al, 2020). So, hypothesis one has been accepted as corporate environmental responsibility has a significant positive effect on corporate financial performance.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…If sample size will be greater than answer may become similar to previous researches. Third, industry competition has positive significant moderating effect on the association between CER and CFP which is similar to previous researches like Hull (2008), who said if competition is high in industry then it will urge companies to attract more customers and investors towards them which is possible if they provide convenience to them by providing safe environment and ultimately it will create long term revenue for the company (Kim & Park, 2021;Lee et al, 2021;Wu et al, 2020). So, hypothesis one has been accepted as corporate environmental responsibility has a significant positive effect on corporate financial performance.…”
Section: Discussionsupporting
confidence: 84%
“…Owing to worldwide environmental transformation and ecological corrosion, surroundings get affected (Amir, Rehman, & Khan, 2020). To get good performance, CER forces organizations to adopt those measures that can protect and improve surrounding and refer them to take responsibility for their environmental protection (Flammer, 2013;Holtbrügge, 2012;Kim & Park, 2021). According to the natural-resource-based view (NRBV), through the positive association between natural reserves and competitive benefit, organizations must give consideration to, and yield from, the growing natural ecological confronts along with fortification.…”
Section: Corporate Environmental Responsibility and Its Effect On Financialmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding purchase intention, the authors of [22] mention that intention predicts future behaviors of consumer behavior, and, in turn, the consumer, when presenting demands, will seek relevant information considering personal experiences and external environments to satisfy them. It usually refers to an individual's willingness to perform a specific act, which is perceived as the premise for direct action [29,30]. Therefore, understanding people's intentions and the reasons they are willing to use a product or service is critical for marketers and marketing stakeholders [25,26].…”
Section: Background 21 Sustainable Purchase Intention and Cinemamentioning
confidence: 99%
“…Attitude refers to people's opinion or perception towards something; in this study, it refers to people who simply have a favorable attitude towards attending the cinema to watch Mexican movies [26]. Previous studies have shown a strong relationship between attitude and intention in the contexts of digital platform use and in the purchase of organic products [27][28][29], green products [30], and luxury goods [31]. Likewise, attitude in an art product context (cinema and television) has been shown to play a key role in explaining the purchase of such products [32].…”
Section: Attitudementioning
confidence: 99%